2000
DOI: 10.1029/gm116p0117
|View full text |Cite
|
Sign up to set email alerts
|

Passive infrared spectroscopic remote sensing of volcanic gases: Ground-based studies at White Island and Ruapehu, New Zealand, and Popocatépetl, Mexico

Abstract: Gaseous volcanic emissions provide important insights on volcanic processes and may aid in predicting eruptive activity, but traditional in situ measurements are prohibitively dangerous at many volcanoes. Here we describe techniques for remotely measuring volcanic gas composition, at ranges up to tens of kilometers, using ground-based passive infrared spectroscopy. The principles of passive in frared spectroscopic remote sensing are discussed, and the effects of thermal contrast on the detectability of gases i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 47 publications
2
26
0
Order By: Relevance
“…For the analysis of spectra at 4 cm −1 taken on 16/17 November 2008 the value 275 K was used and for those taken on 28 May 2009 a temperature of 280 K was chosen. Although an exact value of the plume temperature is not known, the visualization and determination of molecular ratios between SiF 4 and SO 2 are quite insensitive to the plume temperature as described by Love et al (2000) and shown in Sect. 5.1.…”
Section: Atmosmentioning
confidence: 99%
See 2 more Smart Citations
“…For the analysis of spectra at 4 cm −1 taken on 16/17 November 2008 the value 275 K was used and for those taken on 28 May 2009 a temperature of 280 K was chosen. Although an exact value of the plume temperature is not known, the visualization and determination of molecular ratios between SiF 4 and SO 2 are quite insensitive to the plume temperature as described by Love et al (2000) and shown in Sect. 5.1.…”
Section: Atmosmentioning
confidence: 99%
“…According to our knowledge thermal emission spectroscopy to characterize volcanic emissions was applied for the first time in 1996 by Love et al (1998Love et al ( , 2000 and Goff et al (2001). From thermal emission spectroscopy, SO 2 , SiF 4 , H 2 O, CO 2 (Goff et al, 2001) and even HCl (Love et al, 2000) have been determined in volcanic gas plumes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3-6 Several types of remote sensing techniques are available for observing the temporal and spatial characteristics of these gases in plume emitted from various point sources such as power plants and volcanoes, such as Correlation SPECtrometer (COSPEC) method, 7 the SO 2 camera technique, 8 Fourier-Transform spectroscopy in the IR (FT-IR), [9][10][11] and passive differential optical absorption spectroscopy (DOAS). However, these methods do not support simultaneous measurements of multiple trace gases.…”
Section: Introductionmentioning
confidence: 99%
“…This method is usually used to yield the atmospheric constituents and temperature. It is the simplest possible remote measurement of * e-mail: s.cieszczyk@pollub.pl volcanic gases [1]. Additionally, in the case of combustion processes signicant information about the processes can be obtained from their radiative emissions.…”
Section: Introductionmentioning
confidence: 99%